2018
DOI: 10.1111/jdi.12726
|View full text |Cite
|
Sign up to set email alerts
|

Changes in heart rate in patients with type 2 diabetes mellitus after treatment with luseogliflozin: Subanalysis of placebo‐controlled, double‐blind clinical trials

Abstract: We evaluated the changes in heart rate on the treatment with SGLT2 inhibitor, luseogliflozin, in Japanese patients with type 2 diabetes mellitus (T2DM). It is suggested that luseogliflozin can effectively decrease in heart rate in patients with higher baseline.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 6 publications
3
18
1
Order By: Relevance
“…A significant reduction in uric acid levels was seen during treatment with luseogliflozin, consistent with increased urinary excretion of uric acid secondary to luseogliflozin‐induced glycosuria 48 . Taken together, the findings of the current study are consistent with the documented clinical benefits of luseogliflozin in patients with diabetes 49‐54 …”
Section: Discussionsupporting
confidence: 84%
“…A significant reduction in uric acid levels was seen during treatment with luseogliflozin, consistent with increased urinary excretion of uric acid secondary to luseogliflozin‐induced glycosuria 48 . Taken together, the findings of the current study are consistent with the documented clinical benefits of luseogliflozin in patients with diabetes 49‐54 …”
Section: Discussionsupporting
confidence: 84%
“…Despite a drug-induced decrease in blood pressure, it has been reported that SGLT2 inhibitors do not increase heart rate. For example, among patients with baseline heart rates >80 beats/min (bpm), luseogliflozin was associated with a 7.5-bpm decrease in heart rate compared with a 3.9-bpm decrease in placebo-treated patients ( 48 ). Similarly, dapagliflozin did not increase heart rates compared with placebo ( 49 ).…”
Section: Clinical Efficacymentioning
confidence: 99%
“…SGLT2 inhibitors ameliorate excessive sympathetic nervous activity by suppressing afferent signaling from renal sensory nerves through the improvement of metabolic stress in the kidney. As evidence, SGLT2 inhibitors reduce the heart rate in T2 DM patients with a fast heart rate (17).…”
Section: Kidney Stressmentioning
confidence: 86%